Answer:
Part 1) Option C [tex]x^{2}-4[/tex]
Part 2) Option A [tex](x+6)(x-6)[/tex]
Part 3) Option C [tex](2x+9)(2x-9)[/tex]
Part 4) Option C Prime
Part 5) Option C [tex]2(x+3)(x-3)[/tex]
Part 6) Option A [tex]3(x^{2} -7)[/tex]
Step-by-step explanation:
we know that
A difference of square can be factored in the form
[tex]a^{2}-b^{2}=(a+b)(a-b)[/tex]
Part 1) Find the product: [tex](x + 2)( x - 2)[/tex]
Applying difference of square
[tex](x + 2)( x - 2)=x^{2}-2^{2}[/tex]
[tex](x + 2)( x - 2)=x^{2}-4[/tex]
Part 2) Factor Completely: [tex]x^{2} -36[/tex]
Applying difference of square
[tex]x^{2} -36=(x+6)(x-6)[/tex]
Part 3) Factor Completely: [tex]4x^{2} -81[/tex]
Applying difference of square
[tex]4x^{2} -81=(2x+9)(2x-9)[/tex]
Part 4) Factor Completely: [tex]x^{2} +16[/tex]
Is not a difference of square
Is prime
therefore
Is not possible to factored
Part 5) Factor Completely: [tex]2x^{2} -18[/tex]
[tex]2x^{2} -18=2(x^{2} -9)[/tex]
Applying difference of square
[tex]2(x^{2} -9)=2(x+3)(x-3)[/tex]
Part 6) Factor Completely: [tex]3x^{2} -21[/tex]
Is not a difference of square
[tex]3x^{2} -21=3(x^{2} -7)[/tex]